Cultural Heritage Tourism in Malaysia: Issues and Challenges - Ismail, Norhasimah; Masron, Tarmiji; Ahmad, Azizul (EDP Sciences, 2014)
Malaysia is experiencing an incredible pace of tourism development and heritage tourism is one of the tourism branches that have long contributed to appeal the tourist destination and acts as important marketing tool to attract tourist especially with special interests in heritage and arts. Cultural heritage tourism has emerged as a potential form of alternative tourism among both international tourists as well as Malaysian domestic travelers. The difference of ethnics present in Malaysia brought different local knowledge discipline ranging from its architecture, handicrafts, traditional attire, music and dance, which reflects a colorful heritage and an amalgamated culture. There are arise of conflict in management of cultural heritage tourism in Malaysia face by tourism managers, stakeholders, governments, cultural heritage managers and local community itself. In order to maintain, conserve and preserve the resources and assets of cultural heritage in Malaysia, a system or management need to be develop that take into consideration on every issues and challenge, so that the decision making process is reliable to optimize the value of cultural heritage tourism industry in Malaysia. The purpose of this paper is to give an overview and discuss the status, issues and challenge of cultural heritage tourism in Malaysia.